Performance evaluation of wax inhibitor with sodium cloisite through experimental and molecular dynamics simulation (MD) - Priyatachni, Subramanie (2020)
Wax deposition is the formation and growth of solid phase layer that occurs during crude oil production. These wax precipitates regularly known as paraffin and builds up in pipelines and other production equipment. The presence of paraffin wax in crude oil cause many problems and complications in oil and gas industry. In Malaysia, depositions of paraffin wax in the inner and on the surface of production equipment and transportation pipelines have been identified as the utmost challenge during crude oil production. If the paraffin wax is not being removed time to time it can wholly cause a block in the pipeline and eventually stops the flow of the crude oil. The objective of this study is to evaluate the performances of wax inhibitors through cold finger experiment and to elucidate the interaction of wax molecules with wax inhibitor molecules through molecular dynamic (MD) simulation. Four parameters have been considered as follows, effect of cold finger temperature, experimental duration, impeller rotation and amount of nanoparticle loading to confirm the effectiveness of the poly (ethylene-co-vinyl acetate) (EVA) and nanoparticle (NP) blend wax inhibitor. Wax deposited in cold finger was scraped and weighed to calculate the percentage inhibition efficiency (PIE). The behaviour of wax inhibitor molecule with and without incorporation of nanoparticles and wax molecules was simulated in order to investigate the intermolecular interaction through radial distribution analysis (rdf) which drives the formation and deformation of wax using MD simulation. EVA and NP blend shows the best performance to reduce the wax deposition rate based on percentage of inhibition efficiency, PIE and viscosity value. EVA and NP blend successfully reduced wax deposition and viscosity about 80.91 % and 94 % respectively. The minimum amount of wax obtained was at 25 °C proving that cold finger temperature plays important role in altering the wax deposition rate. The n-icosane molecules in crude oil are bonded together to form wax crystals with van der Waals (vdW) interaction between hydrogen 59, H59 and hydrogen 60, H60. The rdf value is shifted from 2.75 Å to 3.25 Å when EVA and NP blend is used as the inhibitor as it offers more functional bonds for wax molecules to interact compared to EVA alone thus reducing the wax-wax interaction. EVA exhibit strong vdW interaction via the oxygen atom in vinyl acetate (VA) compound and this bond is further strengthen by addition of nanoparticle whereby the presence of three functional oxygen bonds in sodium cloisite (Na+) that can form hydrogen bonds with wax molecules. This study presents the incorporation of nanoparticle with wax inhibitors as an efficient mitigation method to overcome wax deposition issue in oil and gas industry.